Analisis Dampak Shut Down US Goverment Tahun 2018 Pada Bursa Efek Indonesia - Choirun Nisful Laili (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
The purpose of this study was to determine the differences in returns, abnormal returns, and cumulative abnormal returns of shares before and after the US govermet 2018 shut down event. The object of research is companies that belong to the LQ-45 stock group on the Indonesia Stock Exchange. Research uses the type of event study. The results of the study using paired sample t-tests showed no differences in stock returns and abnormal returns for periods before and after the 2018 US government shut down event. For cumulative abnormal returns before and after the 2018 US government shut down event, differences were found.